Effects of Energy Efficiency and Renewable Energy Consumption on CO2 Emissions in Sub-Saharan Africa: An Examination of Transmission Channels - Zoungrana, Tibi Didier; Hien, Vlabassolo Wilfred; Yerbanga, Antoine (International Journal of Energy Economics and Policy, 2025)
The aim of this research is to analyze, via transmission channels, the effects of energy efficiency and renewable energy consumption on carbon dioxide (CO2) emissions in sub-Saharan Africa (SSA) over the period 2002-2020. For that, defactored instrumental variables method was used on a sample of 25 sub-Saharan African countries. The results show that energy efficiency, renewable energy consumption and interaction of these variables with transmission variables significantly reduce CO2 emissions in SSA. Governments in this region should invest more in clean and energy-efficient technologies in order to move towards achieving Sustainable Development Goal 7 (SDG 7).